A Mamdani Fuzzy-C4.5 Hybrid Model for River Water Quality Assessment: A Case Study of the Beringin River - Fianti Fianti; Risma Dwi Rahmawati; Sunarno Sunarno; Suharto Linuwih; Siti Wahyuni; Fifin Dewi Ratnasari (JUITA: Jurnal Informatika, 2026)
Urban and industrial activities along the Beringin River in Semarang City cause water pollution in the river. Therefore, assessing water quality is necessary an effort to preserve the environment, safeguard human well-being, and provide early warnings of potential decline. This study used a Mamdani fuzzy logic for development water quality assessment. Input variables consisted of TSS, TDS, Ph, DO, BOD, COD, Nitrate, and Nitrite with water quality as the output. System development was begun by determination of fuzzy set domains for fuzzification and defuzzification. Fuzzy rules were formulated using IF-THEN relationships integrated with C4.5 Algorithm, an algorithm was used to select the most relevant attributes and pruning redundant branches to simplify complex decision-making system, in accordance to the health and environmental standards. The validation of the water quality assessment system was carried out by comparing the Pollution Index (PI) calculation data of 27 data points over a five-year period. The validation results showed accuracy system of 88.9%, with the water quality was categorized as moderately polluted. These findings indicated that the water quality assessment system have high accuracy and can be specifically applied in the Beringin River.